Critique of Macro Basics in Curriculum Planning in the Quran and Hadith Sciences - Ali Reza Fakhary (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Curriculum planning is based on both macro and general issues as well as on the details, and the type of look at each one will have a major impact on the curriculum development and its quality. One of the most important issues in this regard is the need assessment, setting and limiting goals and missions, as well as the issue of evaluation. The strengths and weaknesses of a curriculum return to the strengths and weaknesses of these issues. Therefore, to optimize each educational activity, it is necessary to evaluate each of its components in order to identify the deficiencies by trying to resolve them. An overview of the curriculum of the Quran and Hadith sciences suggests that there is no serious theoretical precision in constructing the principles of curriculum planning, which may be one of the major weaknesses of the discipline and the cause of not making capable students. Planning with no plans and non-compliance with educational standards will not solve the problem, and it will further become a problem along with other problems.